(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
This study aimed to assess the impact of ERP implementation, system upgrades, and disaster recovery strategies on the success of IT projects in complex business environments. The research focused on professionals involved in IT and ERP projects, particularly in sectors requiring the integration of advanced technologies such as SAP solutions and IT infrastructure management. A quantitative approach was used, with data collected through a survey questionnaire targeting project managers, IT officers, and system experts working in ERP and IT systems implementation, including those in SAP consultancy and IT infrastructure management roles. The methodology involved analyzing the responses of professionals who had been directly involved in ERP system implementation, system upgrade evaluations, and the development of business continuity plans. The study used statistical methods to explore the relationships between the independent variables—ERP implementation, system upgrades, and disaster recovery strategies—and the dependent variable, project success. The results demonstrated that effective ERP implementation and system upgrades significantly improved business performance and decision-making processes. Additionally, the implementation of disaster recovery strategies was crucial in reducing recovery time objectives (RTO) and recovery point objectives (RPO), ensuring minimal service disruption. The findings highlighted that a strategic combination of these practices contributed to higher operational resilience, enhanced project delivery, and the successful integration of complex IT systems.